Failure of Herpes Simplex Virus Glycoprotein D Antibodies to Elicit Antibody-Dependent Cell-Mediated Cytotoxicity: Implications for Future Vaccines . (14th July 2022) - Mahant, Aakash Mahant; Guerguis, Sandra; Blevins, Tamara P; Cheshenko, Natalia; Gao, Wei; Anastos, Kathryn; Belshe, Robert B; Herold, Betsy C
Abstract: Background: The glycoprotein D (gD)/AS04 vaccine failed to prevent herpes simplex virus (HSV) 2 in clinical trials. Failure was recapitulated in mice, in which the vaccine elicited neutralizing antibody but not antibody-dependent cell-mediated cytotoxicity (ADCC) responses. Preclinical findings suggest that ADCC is important for protection, but the clinical data are limited. We hypothesized that gD/AS04 and acute HSV-2 infection elicit primarily neutralizing antibodies, whereas ADCC emerges over time. Methods: HSV-specific immunoglobulin G, subclass, function (neutralization, C1q binding and ADCC), and antigenic targets were compared (paired t test or Mann-Whitney U test) at enrollment and after gD/AS04 vaccination, before and after HSV-2 acquisition in vaccine controls, and in an independent cohort with chronic HSV-2 infection. Results: Vaccination elicited only a neutralizing antibody response, whereas acute infection elicited neutralizing and C1q-binding antibodies but not a significant ADCC response. Antibodies to gD were exclusively immunoglobulin G1 and only neutralizing. In contrast, women with chronic HSV-2 infection had significantly greater ADCC responses and targeted a broader range of viral antigens compared with acutely infected or gD/AS04 vaccine recipients ( P < .001). Conclusions: Results from gD/AS04 vaccinated or acutely infected women recapitulate murine findings of limited functional antibody responses, supporting the speculation that vaccines that generate polyfunctional and specifically ADCC responses may be required to prevent HSV-2 acquisition and limit recurrences. Abstract : The glycoprotein D/AS04 vaccine, which failed to prevent herpes simplex virus (HSV) 2 in a large field trial, elicited only neutralizing antibodies. Significant antibody-dependent cell-mediated cytotoxicity responses were detected in women with longstanding HSV-2 infection but not within 6 months of acute infection.